2009
DOI: 10.1111/j.1574-6968.2009.01807.x
|View full text |Cite
|
Sign up to set email alerts
|

Steroids mediate resistance to the bactericidal effect of phosphatidylcholines againstHelicobacter pylori

Abstract: Helicobacter pylori assimilates various steroids as membrane lipid components, but it can also survive in the absence of steroids. It thus remains to be clarified as to why the organism relies on steroid physiologically. In this study, we have found that phosphatidylcholine carrying a linoleic acid molecule or arachidonic acid molecule has the potential to kill steroid-free H. pylori. The bactericidal action of phosphatidylcholines against H. pylori was due to the lytic activity of the phosphatidylcholines the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 37 publications
1
34
0
Order By: Relevance
“…A study by our group in 2009 revealed that dM␤CD protects H. pylori cells from the bactericidal action of unsaturated fatty acids and LPC by inhibiting the absorption of those lipophilic compounds into the cell membranes (23). This suggests that the outer membrane of the H. pylori cell may incorporate dM␤CD by binding to PE and that the dM␤CD so incorporated may prevent the absorption of unsaturated fatty acids and LPC into the H. pylori cell by weakening the hydrophobic interaction between those lipophilic compounds and the outer membrane.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A study by our group in 2009 revealed that dM␤CD protects H. pylori cells from the bactericidal action of unsaturated fatty acids and LPC by inhibiting the absorption of those lipophilic compounds into the cell membranes (23). This suggests that the outer membrane of the H. pylori cell may incorporate dM␤CD by binding to PE and that the dM␤CD so incorporated may prevent the absorption of unsaturated fatty acids and LPC into the H. pylori cell by weakening the hydrophobic interaction between those lipophilic compounds and the outer membrane.…”
Section: Discussionmentioning
confidence: 99%
“…The glucosylation of FC also has been shown to play an important role in the colonization of H. pylori in the stomachs of mice and gerbils (17,28). Our group, meanwhile, has demonstrated that H. pylori retains steroids to reinforce the membrane lipid barrier, with or without glucosylation, and thereby acquires resistance against the bacteriolytic action of phosphatidylcholines (PCs) (23). A recent study by another group has shown that H. pylori expresses further resistance against bile salts (including ceragenins) by absorbing FC, even in the HP0421 (cgt) gene knockout mutant (26).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…80,81 It may also reinforce the bacterial membrane, promoting resistance to toxic host compounds. 82,83 Wunder et al 80 delivered a seminal set of data that helped define the role of membrane-incorporated cholesterol in promoting pathogenesis. They find that H. pylori can sense and move toward cholesterol in its environment at levels as low as 250 μM, extract it from the cholesterol-rich lipid rafts of epithelial cells, glucosylate it by the action of a cholesterol-α-glucosyltransferase, Hp0421, and integrate it into the membrane.…”
Section: Helicobacter Pylori and Cholesterolmentioning
confidence: 99%